Evaluation of health-care utilization in patients with Dravet syndrome and on adjunctive treatment with stiripentol and clobazam - Strzelczyk, Adam; Schubert-Bast, Susanne; Reese, Jens P.; Rosenow, Felix; Stephani, Ulrich; Boor, Rainer (Epilepsy & behavior, 2014)
Dravet syndrome (DS) is a rare, severe childhood epilepsy syndrome that imposes a substantial burden on patients and their caregivers. This study evaluated health-care utilization over a 2-year period in patients with DS at an outpatient clinic of a German epilepsy center. Data on the course of epilepsy, anticonvulsant treatment, and direct costs were recorded using the electronic seizure diary Epivista® and patients' files. We enrolled 13 patients with DS (6 females, mean age: 12.3±7.5years) between 2007 and 2010 and evaluated them during a 1-year baseline. All patients had drug-resistant epilepsy and their seizures failed to improve with a mean number of 6.7±3.4 anticonvulsants. They had an overall mean seizure frequency of 102.1seizures per year (median: 31, range: 3-538) with 43.2GTCSs per year (median: 14, range: 0-228). We estimated the annual total direct costs at €6506±3974 (range: €1174-11,783) per patient with hospitalization (68.9% of total direct costs) as the major cost factor ahead of costs for anticonvulsants (24.0%). For the 1-year follow-up period, less severely affected patients were continued on conventional anticonvulsants (n=4) or switched to adjunctive treatment with stiripentol and clobazam (n=9). In the latter group, six patients (67%) were long-term responders, with between 25% and 100% seizure reduction with respect to either GTCSs or the overall seizure frequency. This reduction in seizure frequency was associated with a shift in the distribution of cost components towards higher medication costs and decreased hospitalization costs. The total direct costs increased by 42.7%, mainly due to the newly introduced stiripentol, with an annual cost of €6610. This study showed that direct costs of patients with DS were above the average European costs of drug-resistant epilepsy in children. Treatment with new anticonvulsants resulted in reduction of seizures and inpatient admissions.